Gravitational Autoreposition for Staged Closure of Omphaloceles - Uecker, Marie; Petersen, Claus; Dingemann, Carmen; Fortmann, Caroline; Ure, Benno M.; Dingemann, Jens (European Journal of Pediatric Surgery, 2020)
Introduction Management strategies for large omphaloceles remain controversial. In this study, we discuss the use of GRAVITAS (gravitational autoreposition sutures), the method used at our institution when successful primary closure is deemed questionable. Patient's primary clinical course and long-term outcomes were analyzed.Materials and Methods This is a single-center retrospective analysis of all consecutive patients with omphaloceles treated between 1997 and 2018. Decision for GRAVITAS was made when the defect was estimated too large for primary closure. Traction sutures were placed in the fascia surrounding the defect and then suspended from the top of the incubator to allow gravitational autoreposition of the herniated organs. Ventilation and muscle relaxation were maintained until secondary closure, which was performed after the obtruding viscera had been reduced by repeated adjustment of the suture's tension. Data are presented as mean ± standard deviation.Results Out of 49 patients with omphaloceles, 12 were treated with GRAVITAS, 33 underwent primary closure, and 4 were treated using Schuster's technique. Mean time to secondary closure after GRAVITAS was 7 ± 10 days. In nine of the patients who had isolated omphalocele, secondary closure was achieved after 4 ± 2 days. Ventilation time was 5 ± 2 days, and time to full feeds was 18 ± 16 days. In three patients (one with Fallot's tetralogy, one with Cantrell's pentalogy, and one with lung hypoplasia), abdominal closure was achieved after 17 ± 15 days. Due to cardiorespiratory comorbidity, ventilation time was >30 days. Five patients received initial closure of the skin and secondary fascial closure after 18 ± 15 months. One patient with prior fascial closure underwent later repair of an abdominal wall hernia. During follow-up (30 ± 35 months), one patient with gastrointestinal obstruction due to adhesions required laparotomy, and one patient with gastroesophageal reflux disease underwent fundoplication.Conclusion GRAVITAS is a feasible method for staged closure of large omphaloceles when successful primary closure is deemed questionable.
Keywords: omphalocele; staged closure; congenital abdominal wall defect